Bone Measurements of Arginine Deficient Broilers Growing under Warm Temperatures - H. T. Dao; A. F. Moss; E. J. Bradbury; R. A. Swick (Tropical Animal Science Journal, 2022)
The effects of L-arginine (Arg) and L-citrulline (Cit) supplementations in an Arg-deficient reduced-protein diet on tibia morphology and mineral composition were investigated in broilers maintained at the thermo-neutral (NT) and cyclic warm temperature (WT). Seven hundred and twenty Ross 308 male broilers were brooded together for the first 7 days and randomly assigned to four dietary treatments with 12 replicates of 15 birds each from days 8 to 35. The dietary treatments were standard protein diet (SP) with 22.3% and 20.9% crude protein in grower and finisher, respectively, an Arg-deficient reduced-protein diet with 2.5% lower protein (RP), and RP added with Arg (RP-Arg) or Cit (RP-Cit) at 0.28%. Dietary treatments were fed from day 8 with average bird’s body weights of 177±3.25 g. Cyclic warm temperature (33 °C ± 1 °C for 6 h per day) was applied in one of the climate-controlled rooms during the finisher phase (21 to 35 day), resulting in a 2 × 4 factorial arrangement of treatments with the factors were the dietary treatment and temperature. Birds fed the RP diet had lower tibia breaking strength (day 28), ash (day 35), and diameter (days 21 and 28) compared to those offered the SP diet (p<0.05). Birds fed the RP diet had lower serum K and tibia B and higher tibia Mn level on day 21; higher serum Ca, P, and Mg, and lower tibia B level on day 28 compared to the SP-fed birds (p<0.05). Supplementation with Arg or Cit compensated for the adverse effects of the RP diet on these traits (p<0.05). Interactions showed tibia diameter decreased in birds fed the SP diet compared to the RP and RP-Cit diets only when raised under cyclic WT on day 35 (p<0.05). Thus, supplementation of Arg or Cit to the RP diet was necessary to support bone morphology and mineralisation under normal and warm temperatures.